Pengaruh Kurs Dollar Amerika, Konsumsi, dan Produksi terhadap Impor Produk Olahan Susu Indonesia - Dewayani, Masari; Kesumajaya, Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Domestic milk production not yet able to fulfill public’s milk consumption in Indonesia so that the government still need to import it in order to fulfill public’s milk consumption. Milk is essential requirement needed by all age group because milk is protein source and it have complete nutrient content and balance. Milk also as source of calcium which benefit to grow of bone and to prevent of osteoporosis.This research purpose to know how the effect of US dollar rate, consumption, and production toward import of milk product in Indonesia period 1991-2012 whether there is effect both in partial and in simultanous. Beside that it also find out the dominant variable which have effect toward import of milk product in 1991 – 2012 by using SPSS program.The result of analysis showed in simultanous the US dollar rate, consumption and production  have significant effect toward import of milk processing product in Indonesia in 1991 – 2012. Partially variable of US dollar and consumption per capita have positive and significant effect toward import of milk product in Indonesia in 1991 – 2012. variabel of production was not significant effect toward import of milk product in Indonesia in 1991 – 2012. The dominant variable have effect toward milk product is consumption per capita.